Using Social Media as A Legitimation Tool in Sustainability Reporting: Evidence from SOEs Listed on the Indonesia Stock Exchange - Rahmansyah, Arif; Mulyany, Ratna; Geumpana, Teuku Aulia (Jurnal Dinamika Akuntansi dan Bisnis, 2023)
The use of social media changes the dynamics of reporting, leading to interactive communication processes where dialogue and engagement with stakeholders can be used to accompany disclosure of information to seek legitimacy. The purpose of this study is to determine the use of social media in the sustainability report in state owned enterprises (SOEs) listed on the Indonesia Stock Exchange as a means of seeking legitimacy from stakeholders. The data obtained can be parsed, checked, and compared with open coding (open coding). The results of data processing are displayed in excel spreadsheet, and processed into diagrams and tables. The results of this study indicate that social media allows companies to build a dialogue about current issues that affect society and the environment. The issues raised on social media by companies from the three platforms mostly consist of community, employees, diversity, gender equality, health, and corruption issues. The findings implicate that social media has been largely used even by SOEs as a legitimation tool for its stakeholders in constructing a dialogue regarding current issues affecting people and the environment.